Collaborating on Web-Based Instruction in Higher Education: Benefits and Risks - Barbara Y. LaCost; Jody Isernhagen; Larry Dlugosh (Educational Considerations, 2000)
The United States spends $600 billion on education of all types each year, making it the second largest industry after health care.